Impact of a Potential 20-Week Abortion Ban on Likelihood of Completing Required Views in Second-Trimester Fetal Anatomy Ultrasound - Henkel, Andrea; Beshar, Isabel; Cahill, Erica P.; Blumenfeld, Yair J.; Chueh, Jane; Shaw, Kate A. (American Journal of Perinatology, 2022)
Objective The aim of this study was to quantify the likelihood of assessing all mandated fetal views during the second-trimester anatomy ultrasound prior to the proposed federal 20-week abortion ban.Study Design Retrospective cohort study of a random sample of 1,983 patients undergoing anatomy ultrasound in 2017 at a tertiary referral center. The difference in proportion of incomplete anatomic surveys prior compared with after 20-week gestation was analyzed using X2 and adjusted logistic regression; difference in mean days elapsed from anomaly diagnosis to termination tested using t-tests and survival analysis.Results Incomplete views were more likely with initial ultrasound before 20 weeks (adjusted relative risk: 1.70; 95% confidence interval: 1.50–1.94); 43.5% versus 26.1% were incomplete before and after 20 weeks, respectively. Fetal structural anomalies were identified in 6.4% (n = 127/1,983) scans, with 38.0% (n = 49) identified at follow-up after initial scan was incomplete. 22.8% (n = 29) with an anomaly terminated.Conclusion A complete assessment of fetal views during an anatomy ultrasound prior to 20-week gestation is often not technically feasible. Legislation limiting abortion to this gestational age would greatly impact patient's ability to make informed choices about their pregnancies.Key Points
Keywords: termination; health policy; ultrasound; fetal anomaly; abortion; antenatal care